In-situ study of InAs quantum dots encapsulated in asymmetric (Al)GaAs confinement barriers - Mercado-Ornelas, C. A.; Espinosa-Vega, L. I.; Cortes-Mestizo, I. E.; Yee-Rendón, C. M.; Eugenio-López, E.; Olvera-Enriquez, J. P.; Perea-Parrales, F. E.; Belio-Manzano, A.; Méndez García, Victor Hugo (Revista Mexicana de Física, 2022)
In this work the self-assembling of InAs quantum dots (QDs) within asymmetric barriers of (Al)GaAs is studied via reflection high energy electron diffraction (RHEED). A comparative study between the AlGaAs/InAs/GaAs interfaces and its mirror-like heterostructure GaAs/InAs/AlGaAs showed significant differences in the self-assembling and capping of the QDs. The critical thickness of InAs QDs results was proven to be larger when it is grown on AlGaAs alloys, compared with the deposition on GaAs layers. This change is explained by the reduced mobility of In atoms on the Al-containing surfaces, for which the QDs density is increased due to the strain relieve. Through the in-situ analysis of diffusion parameters, it is concluded that the mobility of In atoms decreases the mass transport of 2D and 3D precursors that conduces to the self-assembling of the QDs nanoislands, modifying the rate at which the QDs are formed. Further, during the first stages of QDs capping it is observed that the III-V materials intermixing plays a predominant role. The nanoislands are less affected when are covered by AlGaAs in comparison with the GaAs capping, preserving the QDs morphology and avoiding materials alloying. By following the RHEED intensity behavior during the QDs capping, a model was proposed to obtain quantitative parameters for the smoothing process. High resolution x ray diffraction (HRXRD) measurements show the composition of sharp interfaces for the AlGaAs/InAs/GaAs heterostructure. Lastly, numerical simulations were performed to evaluate the strain changes using the experimental information as input data.